Phylogenetic analysis of the envelope protein (domain lll) of dengue 4 viruses Análisis filogenético del dominio III de la proteína de envoltura del virus dengue 4 - Javier Mota; José Ramos-Castañeda; Rebeca Rico-Hesse; Celso Ramos (Instituto Nacional de Salud Pública, 2002)
Objective. To evaluate the genetic variability of domain III of envelope (E) protein and to estimate phylogenetic relationships of dengue 4 (Den-4) viruses isolated in Mexico and from other endemic areas of the world. Material and Methods. A phylogenetic study of domain III of envelope (E) protein of Den-4 viruses was conducted in 1998 using virus strains from Mexico and other parts of the world, isolated in different years. Specific primers were used to amplify by RT-PCR the domain III and to obtain nucleotide sequence. Based on nucleotide and deduced aminoacid sequence, genetic variability was estimated and a phylogenetic tree was generated. To make an easy genetic analysis of domain III region, a Restriction Fragment Length Polymorphism (RFLP) assay was performed, using six restriction enzymes. Results. Study results demonstrate that nucleotide and aminoacid sequence analysis of domain III are similar to those reported from the complete E protein gene. Based on the RFLP analysis of domain III using the restriction enzymes Nla III, Dde I and Cfo I, Den-4 viruses included in this study were clustered into genotypes 1 and 2 previously reported. Conclusions. Study results suggest that domain III may be used as a genetic marker for phylogenetic and molecular epidemiology studies of dengue viruses. Objetivo. Evaluar la variabilidad genética del dominio III de la proteína de envoltura (E) y estimar la relación filogenética de los virus dengue 4 (Den-4) aislados en México y en otras regiones endémicas del mundo. Material y métodos. En el presente trabajo reportamos un estudio filogenético del dominio III de la proteína de envoltura (E) que se realizó en 1998 con virus Den-4 aislados en distintos años en México y en otras partes del mundo. Se usaron oligonucleótidos específicos para amplificar por RT-PCR la región del dominio III y para obtener la secuencia de nucleótidos. Mediante el análisis de la secuencia de nucleótidos y de la secuencia deducida de aminoácidos se estimó la variabilidad genética y se generó un árbol filogenético. Para facilitar el análisis genético del dominio III se usó la técnica basada en el polimorfismo de fragmentos generados con enzimas de restricción (PFER) utilizando seis enzimas de restricción. Resultados. Los datos demuestran que la información del análisis de la secuencia de nucleótidos y de aminoácidos de la región del dominio III es similar a la del gene completo de la proteína E. El análisis de PFER con las enzimas de restricción Nla III, Dde I y Cfo I, mostró que los virus Den-4 incluidos en este estudio se agruparon en los genotipos 1 y 2 reportados previamente. Conclusiones. Los resultados sugieren que el dominio III se puede utilizar como un marcador para estudios filogenéticos y de epidemiología molecular del virus Den-4.